La perception gustative de l’Homme peut-elle varier en fonction de l’état physiologique ? - André Marez; Bruno Simmen; Marie-Odile Monneuse; Louisette Razanamparany; Patrick Pasquet; Claude-Marcel Hladik (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Although studies of humans in a state of hunger or satiety show variations in hedonic responsiveness (preference/aversion) to sugar, the taste recognition thresholds for different substances appear to be stable individual characteristics, as Pangborn, beginning in 1959, observed on a small sample of human subjects. However, a recent study suggests that caloric deprivation is associated with increasing taste sensitivity (as defined by the recognition thresholds) to sugar and salt solutions. Such a variation between taste sensitivity and short-term energy balance was not confirmed by our blind tests with 6 substances including sugars and salt, as well as two bitter products and glycyrrhizin (purified liquorice) on fasting subjects, and on the same subjects after an energy-rich meal. The only variations observed are hedonic values for sucrose that are significantly higher for females in the first phase of the menstrual cycle.